Pemikiran Filosofis (di) Indonesia: Sebuah Telaah Hermeneutis - Bolo, Andreas Doweng (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2019)
Tracing the history of philosophical thoughts in Indonesia might lead to the fact that they build up from the daily experiences of Indonesian people. Philosophical thoughts are born of real situations lived by the people responding to the challenges in their lives. In the effort of tracing the history, one may find the courageous leaders of colonial era and the thinkers emerging after the colonial era who speak against the suppression of humanity in any form, whether in the context of politics, religion, culture, or economy. Indonesian thinkers are people who are fearless and devoting their lives to humanity. This may remind one of the classic slogan sapere aude (dare to think for themselves). In this article, the author correlates experiences, theories, and possibilities towards the future concerning the emergence of philosophical thoughts in Indonesia from a hermeneutical viewpoint. This article walks through the course of outlining an understanding of philosophy, applying hermeneutics to correlate the philocophical outline with the thoughts of Indonesian thinkers, and showing new perspective in seeing the dynamics of philosophical thoughts in Indonesia.